2007
DOI: 10.1590/s1679-87592007000100004
|View full text |Cite
|
Sign up to set email alerts
|

Protozooplankton characterization of two contrasting sites in a tropical coastal ecosystem (Guanabara Bay, RJ)

Abstract: A B S T R A C TMuch time and resources have been invested in understanding plankton dynamics in Guanabara Bay (Brazil), but no attention has been devoted to the protozooplankton. To fulfill this lacuna, abundance and composition of protozooplankton were investigated from January to December -2000 in fortnightly surface water samplings at two distinct water quality sites (Urca -closer to the bay entrance, more saline and cleaner waters; Ramos -inner reaches, hypereutrophic waters). The density at Urca (10 3 -10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The reason why this compartment was virtually absent from our samples remains uncertain. If there was a methodological problem, the possible under sampled HN community could be acting as a link between the autotrophic picoplankton and the microzooplankton, as observed in a previous survey at nearby sites in Guanabara Bay (GOMES et al, 2007). On the other hand, if the HN community at the entrance of Guanabara bay is actually absent, the microzooplankton may be grazing directly upon the autotrophic picoplankton, as already pointed out in previous studies worldwide (e.g.…”
Section: Microzooplanktonmentioning
confidence: 66%
See 1 more Smart Citation
“…The reason why this compartment was virtually absent from our samples remains uncertain. If there was a methodological problem, the possible under sampled HN community could be acting as a link between the autotrophic picoplankton and the microzooplankton, as observed in a previous survey at nearby sites in Guanabara Bay (GOMES et al, 2007). On the other hand, if the HN community at the entrance of Guanabara bay is actually absent, the microzooplankton may be grazing directly upon the autotrophic picoplankton, as already pointed out in previous studies worldwide (e.g.…”
Section: Microzooplanktonmentioning
confidence: 66%
“…This variation is due to the balance between terrestrial influence, i.e., inputs of high loads of nutrients and organic material from riverine sources and from domestic and industrial sewage, and oceanic forces, i.e., strong tidal currents (80 -150 cm s -1 ) at the narrow entrance of the bay (JICA, 1994). The plankton communities of Guanabara Bay have been well studied since the beginning of the XXth century on both short and long term scales, providing a relevant array of information about the dynamics of the autotrophic microplankton (VILLAC; TENENBAUM, 2010 and references therein), bacterioplankton (GUENTHER et al, 2008b), auto-and heterotrophic nanoplankton , microzooplankton (GOMES et al, 2007) and mesozooplankton (e.g. WANDERNESS et al, 1997;VALENTIN et al, 1999;GOMES et al, 2004;SCHWAMBORN et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…There is a highly diverse grazer nanoplankton community in the southeast Brazilian coastal embayments formed mostly by mixotrophic dinoflagellates (Kutner and Sassi, 1979;Sassi and Kutner, 1982;Domingos and Menezes, 1998;Tenenbaum et al, 2006;Villac et al, 2008;Moser et al, 2017) which are possibly the main consumers of Synechococcus, as reported elsewhere (Jeong et al, 2005, and references herein). Indeed, plankton studies in coastal areas of the SBB reported the dominance of heterotrophic nanoflagellates for the carbon biomass (Gomes et al, 2007;Santos et al, 2007). This planktonic structure reflects the meso-oligotrophic conditions of the coastal zone along the SBB where the usual N to P ratios are around 1, limiting the dominance of the primary producers to small photosynthetic cells such as Synecococcus that may rely on sub-micromolar concentrations of nitrogen (Zwirglmaier et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…These changes, in turn, are reflected into all the upper trophic levels. Protozooplankton abundance is higher in the inner hypereutrophic parts of the bay (10 3 –10 5 cell l -1 ) with dominance of small heterotrophic dinoflagellates and naked ciliates, while large marine dinoflagellates were only found at the entrance of the bay ( Gomes et al, 2007 ). This confirms the trend of a shift from autotrophic to heterotrophic microorganisms in the bay.…”
Section: Consequences Of Guanabara Bay Pollution To Higher Trophic Lementioning
confidence: 99%